Finance Research Productivity and Influence. - Borokhovich, Kenneth A (Journal of Finance, 1995)
This study examines differences in finance research productivity and influence across 661 academic institutions over the five-year period from 1989 through 1993. The authors find that forty institutions account for over 50 percent of all articles published by sixteen leading journals over the five-year period; sixty-six institutions account for two-thirds of the articles. Influence is more skewed, with as few as twenty institutions accounting for 50 percent of all citations to articles in these journals. The number of publications and publication influence increase with faculty size and academic accreditation. Prestigious business schools are associated with high publication productivity and influence. Coauthors are Robert J. Bricker, Kelly R. Brunarski, and Betty J. Simkins.